Cerium anomaly in REE pattern of Antarctic eucrite - Shimizu, Hiroshi; Masuda, Akimasa; Tanaka, Tsuyoshi (1983)
P(論文) To examine the weathering effect, we determined abundances of rare-earth elements (REE), Ba and Sr and contents of major elements (MgO, FeO, CaO, MnO and (Na)_2O) for inner and outer parts of the ALH-78132 Antarctic eucrite. It was observed that the inner part of this eucrite (ALH-78132,78) showed a negative Ce anomaly, while all of the outer part specimens (ALH-78132,71a, b, c and 79) displayed positive Ce anomalies. On the other hand, contents of MgO, FeO and CaO for the outer part of the eucrite were similar to those for the inner part of the eucrite. Ce and Nd isotopic ratios were also determined for ALH-78132,71c, 79 and 78. In the ^<143>(Nd)/^<144>(Nd) vs. ^<147>(Sm)/^<144>(Nd) diagram, all points of ALH-78132,71c, 79 and 78 appeared to fall in the chondritic evolution field within the experimental errors. Meanwhile, in the ^<138>(Ce)/^<142>(Ce) vs. ^<138>(La)/^<142>(Ce) diagram, it was observed that the points of the outer part specimens, ALH-78132,71c and 79,deviated from the chondritic lines, while the point of inner part sample of ALH-78132,78 lied in the chondritic range within the experimental uncertainty. These results suggest strongly that the positive Ce anomaly of the Antarctic eucrite is a result of terrestrial weathering. departmental bulletin paper